Acute otitis media management: A survey of European primary care pediatricians - Guadalupe Del Castillo-Aguas; César García-Vera; Jacob Urkin; Marilena Moretto; Mareja Vintar Spreitzer; Pirkko Keronen; Andreas Werner; Laura Reali; Karin Geitmann; Péter Poloskey; Beata Kartousova; Werner Sauseng; et al. (Elsevier, 2023)
Purpose: To describe the management of Acute Otitis Media in European countries, comparing practices between countries and accordance with the American Academy of Pediatrics guidelines. Methods: The study was completed via an internet survey. A coordinator per country obtained the local ethical approval, distributed the survey and collected responses. 2109 questionnaires were completed in 14 European countries. Results were analyzed by comparing answers within and between each country. Results: Otoscope device used varied, including conventional (89%), fiber-optic (19%) and pneumatic (4.9%) otoscopes. Decision to treat: 78.1% (63.8-90.5%) would immediately initiate antibiotics for a 6-month-old with bilateral Acute Otitis Media; 73.2% (47.6%-82.9%) would use a delayed antibiotic therapy in a 25-month-old with bilateral Acute Otitis Media; 50.2% would immediately initiate antibiotic treatment in a first episode of Acute Otitis Media for a 3-year-old and 31.5% would defer antibiotics. Younger pediatricians tend to prescribe more antibiotics: 87.6% vs 77.2%, OR: 2.08 (1.31-3.29). Amoxicillin as a first-line treatment was nearly unanimous (88.5%). Influenza vaccine was recommended by 35.7% of physician, whereas anti-pneumococcus was recommended by 86.0%. Conclusions: Among surveyed pediatricians, the diagnostic tools used and the decision to treat with antibiotics varied. Common practice guidelines for European pediatricians would unify current practices and reduce unnecessary antibiotic use.